Implementation of Society Action Research in Strengthening the Character and Morals of Students at TPQ Al-Mabrur Through Religious Activities - Nur Aida Fitria Kusuma Putri; Nur Khofifatun Nisah; Nadia Salsabela; Erlina Nur Susanti; Dea Nur Syahira (Kawakib: Journal of Multidisciplinary Research, 2025)
This article examines the implementation of Society Action Research (SAR), also known as Participatory Action Research (PAR), as a participatory learning approach to strengthen students’ character and morality at TPQ Al-Mabrur. The main problems identified include the low internalization of religious values among students, limited learning facilities, low motivation, and inconsistent teacher discipline. SAR serves as a practical solution through active involvement of students, teachers, and the community in four core stages: planning, action, observation, and reflection. Religious and social activities such as communal cleaning, Qur’an recitation, public sermons, and charity programs function as media for internalizing values of honesty, discipline, empathy, and responsibility. The findings show significant improvement in students’ religious awareness, discipline, social empathy, and reflective capability. Furthermore, strong collaboration between the TPQ, community, and parents supports the continuity and effectiveness of the program. The study concludes that SAR is a holistic approach integrating cognitive, affective, and psychomotor aspects, making it an essential model for character education in Islamic learning institutions.